Cross-border Cooperation: Current State and Development Trends - Michał BILCZAK (Communications of International Proceedings, 2024)
This research investigates the determinants of cross-border cooperation intensity within the framework of Interreg V-A programs implemented along the internal borders of the European Union. Using correlation analysis and linear regression modeling, the study examines the relationship between funding volumes and cooperation indicators: the number of projects and partnerships. Control variables include the number of participating countries, area, population, and total GDP of the program areas. Results of regression analysis show that a 1% increase in program budget corresponds to a 0.25% growth in projects and a 0.30% increase in partnerships, indicating a moderate positive relationship between financial investments and cooperation intensity. Funding has a slightly stronger influence on network interactions than on project initiation. These findings contribute to understanding cross-border cooperation mechanisms and can inform future EU cohesion policy, while highlighting the need to consider additional influencing factors.
Keywords: Social media marketing; loyalty; customers.